Role of Gd addition on machinability of Al-15%Mg2Si in-situ composite during dry turning - Nanda, Is Prima; Ghandvar, Hamidreza; Idris, Mohd Hasbullah; Hanif, Auliya; Arafat, Andril (Communications in Science and Technology, 2020)
Recently, Al-Mg2Si in-situ composites have achieved considerable attention due to their excellent physical and mechanical properties. In fact, there are some limitations of knowledge regarding the machinability characteristics of these composites - particularly when being inoculated with rare earth additions. This study in turn aimed to investigate the influence of machining parameters as well as Gd addition on the machinability of Al-15%Mg2Si composite. To examine the effect of modifier (1.0 wt. % Gd) and machining parameters (feed rate, cutting speed), microstructural evolution, surface roughness (Ra) and cutting force (Fc) were evaluated during dry turning. The results revealed that Gd addition as modifier element led to better surface roughness and higher cutting force owning to the modification of Mg2Si particle structure as well as the formation of Gd intermetallic compounds.